The art of humane education - Verene, Donald Phillip, 1937- (Cornell University Press, 2002)
In The art of humane education, Donald Phillip Verene presents a new statement of the classical and humanist ideals that he believes should guide education in the liberal arts and sciences. These ideals are lost, he contends, in the corporate atmosphere of the contemporary university, with its emphasis on administration, faculty careerism, and student performance. Verene addresses questions of how and what to teach and offers practical suggestions for the conduct of class sessions, the relationship between teacher and student, the interpretation of texts, and the meaning and use of a canon of great books.